2016
DOI: 10.3390/v8070185
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Four Disinfectants against Ebola Virus on Different Materials

Abstract: The West Africa Ebola virus (EBOV) outbreak has highlighted the need for effective disinfectants capable of reducing viral load in a range of sample types, equipment and settings. Although chlorine-based products are widely used, they can also be damaging to equipment or apparatus that needs continuous use such as aircraft use for transportation of infected people. Two aircraft cleaning solutions were assessed alongside two common laboratory disinfectants in a contact kill assay with EBOV on two aircraft relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Like all lipid-enveloped viruses, CCHFV can be readily inactivated by common fixatives such as 2% glutaraldehyde [41], formalin and paraformaldehyde; chlorine-based disinfectants, such as 1% sodium hypochlorite [41,42]; and other disinfectants, such as hydrogen peroxide and peracetic acid [43,44]. Physical inactivation is also effective, like high temperature (56 °C for 30 min or 60 °C for 15 min) [41], Ultraviolet (1,200 to 3,000 μW/cm 2 ) or low pH (less than 6) [43,45].…”
Section: Resultsmentioning
confidence: 99%
“…Like all lipid-enveloped viruses, CCHFV can be readily inactivated by common fixatives such as 2% glutaraldehyde [41], formalin and paraformaldehyde; chlorine-based disinfectants, such as 1% sodium hypochlorite [41,42]; and other disinfectants, such as hydrogen peroxide and peracetic acid [43,44]. Physical inactivation is also effective, like high temperature (56 °C for 30 min or 60 °C for 15 min) [41], Ultraviolet (1,200 to 3,000 μW/cm 2 ) or low pH (less than 6) [43,45].…”
Section: Resultsmentioning
confidence: 99%
“…53 Using RT-PCR, Cook et al 54 demonstrated that Ebola virus outbreak variants dried with an organic soil load on a stainless steel carrier were inert after 5 minutes exposure to sodium hypochlorite (≥0.5%) and after 2.5 minutes exposure to 70% ethanol. Smither et al 55 confirmed the activity of sodium hypochlorite; 10 4 Ebola viruses as measured by PCR were inactivated by 0.75% sodium hypochlorite with 10 minutes contact time. In a later study, Smither et al 56 reported that multiple disinfectants (ie, 0.5% hypochlorite, 10% hypochlorite, 5% peracetic acid, 70% ethanol) were effective against dried cell culture medium containing Ebola virus.…”
Section: Susceptibility To Germicidesmentioning
confidence: 90%
“…Sodium hypochlorite 0.5% solutions are recommended by the CDC 18 as an example of a suitable disinfectant solution for hemorrhagic fever viruses. Smither et al 19 use a similar experimental design (i.e., a combination of TCID 50 assay and passage of neutralized solutions in flasks to rule out residual infectious virus) to study the disinfection of Ebola virus Yambuku-Ecran (EBOV-Ecran) on aluminum carriers by 0.75% NaOCl in tap water for 10 min contact time. In this case, complete inactivation of the 1.5 × 10 5 TCID 50 /mL dried on the carrier was achieved 19 .…”
Section: Discussionmentioning
confidence: 99%